Programa de tutoría virtual para estudiantes universitarios del curso comprensión y redacción de textos - Álvarez Gonzaga, Braulio Ricardo (2021)
The objective of this research was to demonstrate the impact of the implementation of a virtual tutoring program (E-tutorials) on the academic performance of the students of the Comprehension and text writing course at a private university in Peru. The research approach was quantitative, with a test and post-test pre-experimental research design for a single group. The sample consisted of 28 students selected under the non-probabilistic method for convenience and using the student's t hypothesis test method for related samples. The mentoring program used Blackboard as a Learning Management System (LMS) and Coggle as an online tool for organizing ideas. Likewise, the program consisted of a total of 10 sessions. The results showed an increase of 4 points in the average grade (15) and increasing to 57% and 11% the students with Good and Excellent levels of learning achievement respectively. The research concluded that the implementation of the academic tutoring program has a positive impact on the academic performance of students and can be extended to other critical courses.